Developing Integrated Pest Management for Pomelo Farmers in Baan Paengpuay Community, Buriram Province, Thailand - Nilsri, Siraprapa; Panpakdee, Chaiteera (Area Based Development Research Journal, 2024)
Pomelo farmers in Ban Paengpuay, Nangrong District, Buriram Province, Thailand faced challenges due to pest outbreaks, leading to reduced pomelo quality and financial losses. This study aimed to enhance the pest management skills of pomelo farmers and assess the resulting impact. Thirty farmers were selected to participate in the project, which unfolded through the processes of community information gathering, implementation of integrated pest management, and knowledge exchange. Initial steps involved gathering insights from the community to plan project operations. This included collecting community data, organizing forums for diverse perspectives, and devising plans for knowledge transfer. Agricultural extension services helped diagnose plant diseases and pests, identify nutrient deficiencies, and introduce integrated pest management techniques for pomelo cultivation. The second phase focused on implementing pest management techniques tailored to pomelo plots. Methods included mechanical pest control, moth traps with molasses, sticky glue traps, fruit wrapping, and biological pest management using Bacillus subtilis, Bacillus thuringiensis, and Trichoderma Metarhizium. In the third phase, the project facilitated knowledge exchange among participants. Results showed significant improvements, with pomelo production increasing by 85.21 percent. Chemical usage decreased, resulting in savings of 1,200 to 1,400 Baht per Rai (approximately 234.38-273.44 USD per hectare). Production costs decreased by 2.46 to 2.67 percent, and compliance with Good Agricultural Practices (GAP) standards increased by 30 percent, with 11 farmers obtaining certification. Furthermore, pomelo farmers showed a significant increase in knowledge, with a 124.04 percent improvement. This led to better problem analysis skills and increased capacity for exchanging insights. Participants also demonstrated higher confidence and commitment to self-improvement and the advancement of pomelo production practices.